Factors Affecting the Business Performance of the Food Processing Industry in the Capital City of LuangPrabang: https://doi.org/10.69692/SUJMRD100401 - vannaly, Lobee; Keobualaphet, Soulideth; Phimphisan, Thavixay (Souphanouvong University Journal Multidisciplinary Research and Development, 2024)
The purpose of this study is to study the business conditions of the food processing industry and the factors that affect the operation of the food processing industry in the capital city of Prabang with a sample group of 65 business units and used a questionnaire to collect all the data from the sample group and analyze the data with the statistical program SPSS version 2025 to obtain statistical values ​​for descriptive data, percentage values, average values, standard deviations and calculation of correlation coefficients, the results of the study are as follows: The situation the food processing industry in the capital city of Prabang is still mostly owned by small-scale individuals with little investment value, produced mainly for domestic use. As for the factors that affect the food processing industry in Luang Prabang, there are 3 factors that have a negative effect: marketing factors (X2), financial resources factors (X5), cultural and social factors (X10) with a statistical significance level of 0.05. For other factors, there is no effect with a statistical significance level of 0.05.